Penerapan Model Pembelajaran Terbalik Terhadap Hasil Belajar Siswa Pada Materi Hidrokarbon Di Kelas XI SMA Negeri 7 Manado - Puasa, Devita Sonia; Lumingkewas, Sonny (General Chemistry Journal, 2024)
The aim of this research is to determine the improvement in chemistry learning outcomes of high school students after implementing the flipped learning model. The design of this research is a pre-experimental design (One Group Pretest-Posttest Design). This research was carried out at SMA Negeri 7 Manado, Class XI-J, academic year 2023-2024. As an experimental class with 25 students. Data collection was carried out by giving a pretest before the learning process was carried out and a posstest after the learning process. The research data obtained was that the difference between the average pretest and posttest scores in the experimental class was 48,24. The average pretest score is 30,04 while the average posttest score is 78,28. Before carrying out the one sampel t-test, a normality test was first carried out and it was found that the data was normally distributed. Next, it was tested using the t-test, the result obtained were thiting =-19,09 and tiabel = 2,0106. Tcount>Ttable It can be concluded that the increase in student chemistry learning out comes in hydrocarbon material in class taught the orevious one.